Analysis of Boron Arsenide (BAs) Band Gap Energy Experimental Results vs DFT-Based Calculations - Muhammad Dipa Pramudita Budiyana; Muhammad Ziddan Rachman; Pina Pitriana; Diah Mulhayatiah (Department of Physics Education, Universitas Mataram, 2026)
This study aims to analyze the density of states (DOS) of boron arsenide (BAs) using two types of pseudopotentials, namely PBE ultrasoft and PBE-PAW, within the framework of density functional theory (DFT). The resulting DOS profiles show that both methods are able to capture the fundamental electronic characteristics of the material, with similar energy distribution patterns, although differences are observed in the detailed features of the curves. The PBE-PAW method produces smoother and more representative results near the atomic nucleus, whereas the PBE ultrasoft approach exhibits sharper and more fluctuating peaks. Around the Fermi energy level, the density of states approaches zero, indicating the semiconducting nature of the material. The estimated band gap is in the range of 1.5–2.5 eV, suggesting that BAs has potential applications in electronic devices, sensors, and photovoltaic technologies. Based on these findings, further studies are recommended to validate the band gap using hybrid functionals or the GW approximation, to investigate phonon behavior and thermal conductivity, and to optimize pseudopotential selection for high-precision electronic property calculations in future device-oriented applications.